2019
DOI: 10.3390/ijms20071714
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenols as Immunomodulatory Compounds in the Tumor Microenvironment: Friends or Foes?

Abstract: Polyphenols are natural antioxidant compounds ubiquitously found in plants and, thus, ever present in human nutrition (tea, wine, chocolate, fruits and vegetables are typical examples of polyphenol-rich foods). Widespread evidence indicate that polyphenols exert strong antioxidant, anti-inflammatory, anti-microbial and anti-cancer activities, and thus, they are generally regarded to as all-purpose beneficial nutraceuticals or supplements whose use can only have a positive influence on the body. A closer look t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 120 publications
1
58
0
2
Order By: Relevance
“…Several studies have shown how polyphenols target multiple inflammatory components and lead to anti-inflammatory mechanisms and/or inflammation antagonism. Further, polyphenols today represent also promising candidates for the therapy of autoimmune diseases [43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown how polyphenols target multiple inflammatory components and lead to anti-inflammatory mechanisms and/or inflammation antagonism. Further, polyphenols today represent also promising candidates for the therapy of autoimmune diseases [43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…All this was expected. Widespread evidence shows that polyphenols possess predominantly anti-oxidant, anti-inflammatory and immunomodulatory properties in both humans and farm animal species including cattle; hence, they are beneficial all-purpose nutraceuticals or supplements [45,46,88]. Polyphenols inhibit NF-ÎșB, PI3K/Akt, MAPKs, and arachidonic acid-dependent signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because glioblastoma tumors are chemotherapy-resistant with limited treatment options, investigation on new combination therapies or cancer immunotherapy has been prioritized by several research groups [47][48][49] . Recent evidence from numerous laboratories suggests that phytochemicals affect the immune response [50][51][52][53] . Gao et al 54 reported the effects of polyphenols on the development of several lymphocytic responses in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…In studies where model antigens have been administered in animal models, it has been reported that curcumin supplementation increased T follicular helper cells and germinal centre B cells as well as subsequent IgG production [129]. The data on effects of polyphenols on immune cells is increasing, especially in the context of cancer [130], with a lot of research understandably focusing on the effects on Tregs [131]. Modulating this cell type is especially important for ovarian cancer [132][133][134].…”
Section: Curcuminmentioning
confidence: 99%